2017
DOI: 10.1016/j.enbuild.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of a thermoelectric heat exchange module for domestic space heating

Abstract: The overall aim of this work is to develop a thermoelectric (TE) heating system powered by renewable energy that could compete, in the future, with current domestic heating system to reduce the greenhouse gas emissions. In this paper, our results suggest that TE modules can potentially be a solution for domestic indoor space heating whilst using renewable electricity. The test results of the space heating application of TE modules in a laboratory environment (19 • C-21 • C) and outside courtyard low-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The number of nodes is an input value and it affects the interval of calculation time for numerical simulation. the stable analysis condition, the time interval (Δt) must be higher than the minimum time step in Equation (31). The minimum time interval purposes to avoid the denominator becoming zero in the equations from the finite difference method (FDM).…”
Section: Discretization Using the Finite Difference Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of nodes is an input value and it affects the interval of calculation time for numerical simulation. the stable analysis condition, the time interval (Δt) must be higher than the minimum time step in Equation (31). The minimum time interval purposes to avoid the denominator becoming zero in the equations from the finite difference method (FDM).…”
Section: Discretization Using the Finite Difference Methodsmentioning
confidence: 99%
“…The results indicated that a TEM can save the operation energy for heating by up to 64% compared with the electric heater. From the other thermoelectric heating system, it showed a COP of >2 when ∆T between the hot and cold sides was <20 • C [31]. Sun et al [32] proposed a radiant heating terminal based on a TEM and a flat heat pipe and evaluated its performance through an experimental study.…”
Section: Introductionmentioning
confidence: 99%
“…2 The TE module will generate a voltage difference when temperature difference exists across the module, thereby producing electricity in external circuit. 3 Note that commercial thermoelectric modules are widely applied to energy harvesting applications such as photovoltaic power generation system, [4][5][6] vehicle exhaust, [7][8][9][10][11] human body heat recovery, 12 residential heating system, [13][14][15] biomass stove and furnace, 16,17 wireless sensors, 18,19 and processing chips. 20,21 For large-scale applications, Zhang et al 5 evaluated the efficiency of hybrid systems with different photovoltaic (PV) cells including crystalline silicon PV, silicon thin-film PV, polymer PV, and copper indium gallium selenide PV.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that their proposed system consumed 55 to 64% less energy compared with a conventional electric air heater. Wang et al [12] suggested a thermoelectric heating system powered by PV and a micro wind turbine. Their system showed energy savings of 64% and CO 2 emission reductions of 4305.4 kg/year.…”
Section: Introductionmentioning
confidence: 99%